Encyclopedia of social and cultural anthropology - Spencer, Jonathan;Barnard, Alan (London, United Kingdom : Routledge, 1996)
This is the only encyclopedia of social and cultural anthropology to cover fully the many important areas of overlap between anthropology and related disciplines. This work also covers key terms, ideas and people, thus eliminating the need to refer to other books for specific definitions or biographies.
I. Acknowledgements -- II. Introduction -- III. How to use this book -- IV. List of entries -- V. List of contributors -- VI. Analytical table of contents -- VII. Contributions by author.
Includes bibliographical references and index.
Keywords: ENCYCLOPEDIAS